![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(1,\frac{2}{3}+\frac{4}{9}+\frac{1}{5}+\frac{2}{15}+\frac{3}{2}-\frac{17}{18}\)
\(< =>\frac{4}{9}+\frac{3}{2}+\left(\frac{2}{3}+\frac{1}{5}+\frac{2}{15}\right)-\frac{17}{18}\)
\(< =>\frac{8}{18}+\frac{27}{18}+\left(\frac{10}{15}+\frac{3}{15}+\frac{2}{15}\right)-\frac{17}{18}\)
\(< =>\frac{35}{18}+1-\frac{17}{18}\)
\(< =>\frac{53}{18}-\frac{17}{18}\)
\(< =>2\)
\(2,\frac{13}{28}\cdot\frac{5}{12}-\frac{5}{28}\cdot\frac{1}{12}\)
\(< =>\left(\frac{13}{28}-\frac{5}{28}\right)\cdot\left(\frac{5}{12}-\frac{1}{12}\right)\)
\(< =>\frac{2}{7}\cdot\frac{1}{3}\)
\(< =>\frac{2}{21}\)
\(3,\frac{19}{4}\cdot\frac{15}{23}-\frac{15}{4}\cdot\frac{7}{23}+\frac{15}{4}\cdot\frac{11}{23}\)
\(< =>\frac{285}{92}-\frac{105}{92}+\frac{165}{92}\)
\(< =>\frac{15}{4}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
( 3/4 . x + 1 ) : ( -4 ) = -1/28
<=> 3/4 . x + 1 = -1/28 . ( -4 )
<=> 3/4 . x + 1 = 1/7
<=> 3/4 . x = 1/7 - 1
<=> 3/4 . x = -6/7
<=> x = -6/7 . 4/3
<=> x = -8/7
Vậy x = -8/7
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\Rightarrow\) 3x/7 + 1 = 1/112
\(\Rightarrow\) 3x/7 = -111/112
\(\Rightarrow\) 3x = -111/16
\(\Rightarrow\) x = -37/16
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\left(\frac{3}{7}\cdot x+1\right)\text{ : }\left(-4\right)=-\frac{1}{28}\)
\(\frac{3}{7}\cdot x+1=-\frac{1}{28}\text{ }\cdot\left(-4\right)\)
\(\frac{3}{7}\cdot x+1=\frac{1}{7}\)
\(\frac{3}{7}\cdot x=\frac{1}{7}-1\)
\(\frac{3}{7}\cdot x=-\frac{6}{7}\)
\(x=-\frac{6}{7}\text{ : }\frac{3}{7}\)
\(x=-2\)
\(\left(\frac{3}{7}\cdot x+1\right)\text{ : }\left(-4\right)=-\frac{1}{28}\)
\(\frac{3}{7}\cdot x+1=-\frac{1}{28}\text{ }\cdot\left(-4\right)\)
\(\frac{3}{7}\cdot x+1=\frac{1}{7}\)
\(\frac{3}{7}\cdot x=\frac{1}{7}-1\)
\(\frac{3}{7}\cdot x=-\frac{6}{7}\)
\(x=-\frac{6}{7}\text{ : }\frac{3}{7}\)
\(x=-2\)